Interethnic Genetic Differentiation: GM Polymorphism in Eastern Senegal - (:unkn) unknown (My University, 1990)
Analysis of GM polymorphism has been performed on 1,806 individuals representing three sympatric ethnic groups--Bedik, Fulani, and Mandenkalu--of eastern Senegal. Haplotype frequencies estimated by maximum likelihood have been used to compute common genetic pools between the three samples and a number of other sub-Saharan African populations. Despite extreme linguistic and sociocultural differentiations and very high levels of endogamy, especially in the Bedik and Niokholo Mandenkalu, the three populations share about 90%-95% of their haplotype frequencies in a system which commonly provides strong genetic differentiations. This supports the view that, despite its importance at a large continental scale level, as it is discussed for a set of populations from many regions of sub-Saharan Africa, sociocultural differentiation usually has little effect on local genetic diversity.
Keywords: African Research